Pengaruh Berbagai Jenis Pupuk Kandang Terhadap Pertumbuhan Dan Hasil Dua Varietas Tanaman Kangkung (Ipomoea Aquatica L.) - Saepudin, Deden; Noertjahyani; Komariah, Ai (Fakultas Pertanian Universitas Winaya Mukti, 2025)
This study focuses on the effects of different organic manures on the growth and yield of two varieties of water spinach (Ipomoea aquatica L.). The objective was to assess the influence of various types of organic fertilizers, such as chicken, and goat manure, on plant height, leaf number, and yield performance. A field experiment was conducted using a randomized factorial block design (RCBD) with four replications. The results demonstrated that chicken manure significantly increased plant height and leaf number, whereas goat manure resulted in the highest yield. Both varieties responded differently to each type of manure, with variety A showing better performance in yield, while variety B excelled in vegetative growth. These findings suggest that selecting the appropriate organic fertilizer is essential to optimize the growth and yield of water spinach. Further research is recommended to explore long-term effects on soil health. Keywords: organic manure; water spinach; growth performance; yield; varietal response